2019
DOI: 10.1097/jom.0000000000001735
|View full text |Cite
|
Sign up to set email alerts
|

The National Institute for Occupational Safety and Health B Reader Certification Program—An Update Report (1987 to 2018) and Future Directions

Abstract: Objective:The National Institute for Occupational Safety and Health (NIOSH) B Reader Program provides the opportunity for physicians to demonstrate proficiency in the International Labour Office (ILO) system for classifying radiographs of pneumoconioses. We summarize trends in participation and examinee attributes and performance during 1987 to 2018. Methods: Since 1987, NIOSH has maintained details of examinees and examinations. Attributes of examinees and their examination performance were summarized. Simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…This finding was very similar to that observed in the U.S. B Reader program. Studies reported that physicians generally classify pleural changes poorly compared with parenchymal lesions, and this nature was the same for physicians who passed or failed the B Reader examinations 22 , 23 ) . Without specific radiological expertise, the detection of pleural plaques in a chest radiograph becomes challenging.…”
Section: Discussionmentioning
confidence: 98%
“…This finding was very similar to that observed in the U.S. B Reader program. Studies reported that physicians generally classify pleural changes poorly compared with parenchymal lesions, and this nature was the same for physicians who passed or failed the B Reader examinations 22 , 23 ) . Without specific radiological expertise, the detection of pleural plaques in a chest radiograph becomes challenging.…”
Section: Discussionmentioning
confidence: 98%
“…As its name implies, “B” Readers were initially called upon to confirm suspected features of pneumoconiosis in a second-opinion capacity 12 . The program today dispenses with the preceding “A” Readers and instead relies upon a cadre of highly trained B Readers to independently establish findings of CWP 13 . Since 1976, the program has sought to minimize interobserver variability through a rigorous certification process, evaluating candidates on the basis of their ability to categorize images according to the International Labour Organization (ILO) International Classification of Radiographs of Pneumoconioses 14 …”
Section: From Pathology To Policymentioning
confidence: 99%
“…8 There was lack of a quality assurance programme and of adherence to international standards. The B reader programme using chest radiographs which is used in the USA and is evidence based and relies on regular clinician training [53][54][55] was not in operation, and no quality control programme for clinician competency was followed.…”
Section: Improving Health Record Documentation and Interpretationmentioning
confidence: 99%